PERFORMANCE ANALYSIS OF BANJAR SUGIHAN ROAD (STA 0+000-03+000) DIRECTION TO BENOWO, SURABAYA CITY, EAST JAVA PROVINCE USING MKJI 1997 METHOD - Romadhon, Adam; Fatmawati, Laily Endah; Hartatik, Nurani (Jurnal Teknik Sipil, 2023)
Transportation is important as a tool for to go everyday. The increased demand for transportation causes an increase in traffic flow and volume of vehicles which will then cause congestion. One of the traffic jams that occur in the city of Surabaya is on the Banjar Sugihan road. The purpose of this study is to review and analyze the density of traffic flow that occurs on the Banjar Sugihan road, so that it can solve congestion problems and improve services. The method in this study was carried out by conducting traffic surveys to collect primary data which was carried out for three days during rush hour (06.00-17.00) which was guided by the 2014 PKJI. This research resulted in a large volume of vehicles, large capacity roads, as well as the performance of the Banjar Sugihan highway section. From the results of the study it can be concluded that the Banjar Sugihan highway is a road that is densely packed with vehicles, the performance of the Banjar Sugihan Street section has a forced or jammed flow, low speed, volume below capacity. The queues were long and there were big obstacles.